The Transformation of ʿIlm al-Kalām Methodology: An Epistemological Shift from Theocentrism to Anthropocentrism in the Context of Modernity - Ruzi Haryadi; Nunu Burhanuddin (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
Historically, ʿilm al-kalām developed as a theological discipline aimed at safeguarding the coherence of Islamic creed through rational argumentation grounded in a theocentric and apologetic orientation. However, the dynamics of modernity—marked by historical consciousness, social complexity, and increasing ethical demands—have challenged the adequacy of classical kalām methodology in addressing contemporary human problems. This article examines how the methodology of ʿilm al-kalām has undergone an epistemological transformation from a theocentric orientation toward a more anthropocentric approach within the context of modernity. Employing a qualitative conceptual approach and a critical–hermeneutical framework, the study analyzes the epistemological limitations of classical kalām and the direction of its modern reconstruction. The findings indicate that anthropocentrism in modern kalām is not intended to replace divine transcendence, but rather to reaffirm the role of human beings as active epistemological subjects in interpreting and actualizing divine values within historical and social realities. The study concludes that the transformation of kalām methodology enables Islamic theology to function as a reflective discipline that bridges the normative authority of revelation with issues of justice, moral responsibility, and contemporary human challenges without abandoning its theological foundations.